Eu3+-centered luminescence as a probe for visualizing different carrier functions of aggregated triblock copolymers F-68, F-127 and P-123 - Akhmadeev, Bulat S.; Shvedova, Anastasiya E.; Mambetova, Gulnaz Sh; Sudakova, Svetlana N.; Retyunskaya, Olga O.; Elistratova, Julia G.; Syakaev, Victor V.; Podyachev, Sergey N.; Mustafina, Asiya R. (Journal of molecular liquids, 2025)
[Display omitted] •Water-insoluble ligand is incorporated into micelles of P-123, F-127 and F-68.•The structure of Pluronics affects the complexation of the ligand with Eu3+ ions.•The time dependence of Eu3+ luminescence is specific for each Pluronic.•Eu3+ luminescence visualizes differences in the functions of Pluronic micelle carriers.•The use of Gd3+ ions as paramagnetic probes confirms the above trends. In this work, we demonstrate the transformation of a newly synthesized water-insoluble nonyloxy-substituted bis-1,3-diketone calix[4]arene into a water-soluble form by incorporating it into aggregates of Pluronics P-123, F-127, and F-68. The presence of two 1,3-diketo groups attached to the upper rim of the calix[4]arene backbone via the carbonyl carbon atom causes specific complexation of this ligand with Eu3+ ions, accompanied by the sensitizing of Eu3+-luminescence. Notably, the luminescence response of the Eu3+-ligand complex is strongly influenced by the structure of the Pluronics. In P-123 aggregates, the complexation induces a luminescent response that gradually increases over time and stabilizes at a steady level. In contrast, F-68 aggregates produce only a weak luminescent response upon complexation. A unique behavior is observed in F-127 aggregates, where the Eu3+ luminescence first increases and then decreases over time, suggesting a dynamic instability in the micellar environment. Further insights into these phenomena are provided by the hydration numbers of the Eu3+ complexes within the P-123@5 and F-127@5 aggregates, typical for micellar systems. These measurements reveal structural differences between the aggregates, confirming the reduced stability of F-127 micelles as carriers of the Eu3+-ligand complex. Magnetic relaxation rate measurements, performed with Gd3+ ions as paramagnetic probes, corroborate these findings and align with literature-reported differences in the load-bearing capacities of these micellar systems.